Ich will dich fragen ... Simone Weil im Gespräch mit Hiob (lectio difficilior, 2006)
“Affliction“ and “attentiveness“ are central categories in the life and thinking of the French philosopher Simone Weil (1909–1943). Using them as guiding aspects when reading the Book of Job, two implications might be noticed: Affliction (malheur) with its bodily, mental and social dimensions provides an insight into the human condition. Human beings are subjected to an order of creation which does not distinguish between just and unjust people. Furthermore: Those who are not afflicted have the choice of devoting their attentiveness (attention) to affliction. When being distracted with pain (like Job) there is no escape from misery. Attentiveness means abdication of imagination in order to focus on reality – which sometimes is contradictory – and to accept it the way it is. Attentiveness towards an afflicted person re-establishes his or her personal existence. The voices in the Book of Job are a challenge to attend to human beings in debased situations – this can be understood as a feministic option.